Controlling factors for shale gas enrichment and their implications for favorable exploration areas: Insights from the Wufeng–Longmaxi Formations, Southern Sichuan, China - Zhenwei Zou; Jinghao Fu; Hu Li; Yongyang Liu; Chenglin Zhang; Ziqiang Xia; Cunhui Fan (PLoS ONE, 2025)
The exploration and development of shale gas in the Wufeng-Longmaxi Formations (WF-LMX FM) of the Southern Sichuan Basin exhibit pronounced spatial heterogeneity with 3–5 fold gas content variations in strata meeting identical static thresholds (TOC > 2.5wt.%, porosity >5%). This exposes a fundamental disconnect in conventional models that dissociate geochemical potential from tectonic preservation dynamics in post-mature shale systems (Ro > 3.0%). This spatiotemporal decoupling is resolved through process-contingent integration of three critical determinants: thermal maturation trajectories, hydrocarbon generation-preservation windows, and multi-phase tectonic stress imprinting, with fracture connectivity enhancement observed at reduced brittleness thresholds (~35%) via pre-existing microfracture networks inherited from multi-phase deformation events. This study establishes a pioneering multivariate evaluation framework integrating well logs, 3D seismic interpretation, and experimental petrology to decode five governing parameters: Total Organic Carbon (TOC), thermal maturity (Ro), porosity, mineral brittleness, and a preservation potential index (SP) that resolves TOC-Ro-gas content decoupling by quantifying fault throw/erosion rate equilibrium calibrated with shale bed thickness anomalies. Systematic analysis reveals that optimal enrichment necessitates threshold recalibration beyond static paradigms-TOC > 4.0wt.% redefines hydrocarbon potential in high-maturity regimes, while the 3.0-4.0% Ro window balances organic porosity evolution against carbon deposition-induced occlusion. Reservoir viability is further constrained by >4.5% porosity for gas storage capacity and >40% brittle minerals for fracture sustainability. The SP index, incorporating erosional magnitude and fault connectivity, identifies two critical risk zones near the Changning anticline and northern Luzhou, where neotectonic fault reactivation disrupts overpressure maintenance. Spatial synthesis of these constraints delineates two strategic exploration targets: the NW-SE trending Jianwu-Weiyuan slope system exhibiting optimal thermal-structural synergy, and the Luzhou northern anticlinal cluster where fault sealing sustains preservation efficacy. This model resolves the “geochemical preservation paradox” through dynamic process coupling, establishing a transformative paradigm for deep shale gas exploration in thrust-fold terrains.